Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find \((fg)\left(-\frac{1}{9}\right)\), we will follow these steps systematically:
1. Determine the function \(g(x)\)
- Given \( g(x) = 9x + 1 \)
- We need to substitute \(x = -\frac{1}{9}\) into \( g(x) \).
2. Evaluate \( g\left( -\frac{1}{9} \right) \)
- Substitute \( x = -\frac{1}{9} \) into \( g(x) = 9x + 1 \):
[tex]\[ g\left( -\frac{1}{9} \right) = 9 \left( -\frac{1}{9} \right) + 1 \][/tex]
[tex]\[ g\left( -\frac{1}{9} \right) = -1 + 1 = 0 \][/tex]
- So, \( g\left( -\frac{1}{9} \right) = 0 \).
3. Determine the function \( f(x) \)
- Given \( f(x) = x^2 - 10 \)
- We need to substitute \( x = 0 \) (the result from the previous step) into \( f(x) \).
4. Evaluate \( f(g(x)) \) or \( f(g\left( -\frac{1}{9} \right)) \)
- We need to find \( f(0) \):
[tex]\[ f(0) = 0^2 - 10 = 0 - 10 = -10 \][/tex]
So, \((fg)\left( -\frac{1}{9} \right) = -10\).
Thus, the correct choice is:
A. [tex]\((fg)\left( -\frac{1}{9} \right) = -10\)[/tex]
1. Determine the function \(g(x)\)
- Given \( g(x) = 9x + 1 \)
- We need to substitute \(x = -\frac{1}{9}\) into \( g(x) \).
2. Evaluate \( g\left( -\frac{1}{9} \right) \)
- Substitute \( x = -\frac{1}{9} \) into \( g(x) = 9x + 1 \):
[tex]\[ g\left( -\frac{1}{9} \right) = 9 \left( -\frac{1}{9} \right) + 1 \][/tex]
[tex]\[ g\left( -\frac{1}{9} \right) = -1 + 1 = 0 \][/tex]
- So, \( g\left( -\frac{1}{9} \right) = 0 \).
3. Determine the function \( f(x) \)
- Given \( f(x) = x^2 - 10 \)
- We need to substitute \( x = 0 \) (the result from the previous step) into \( f(x) \).
4. Evaluate \( f(g(x)) \) or \( f(g\left( -\frac{1}{9} \right)) \)
- We need to find \( f(0) \):
[tex]\[ f(0) = 0^2 - 10 = 0 - 10 = -10 \][/tex]
So, \((fg)\left( -\frac{1}{9} \right) = -10\).
Thus, the correct choice is:
A. [tex]\((fg)\left( -\frac{1}{9} \right) = -10\)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.